Application of Ubiquitous Power Internet of Things and IPv6 Technology in Wireless Access Terminal and Intelligent Meter Reading Application. Issue 2 (February 2021) - Wang, Yawen; Guo, Feng; Yao, Weiqing; Deng, Guoru; Liao, Rongtao; Hu, Shuai; Jin, Bo; Meng, Haohua; Xiao, Dongling
Abstract: Power is the basis of the development of enterprises and even the country. In recent years, the demand for power in China is increasing. Wireless access terminals and intelligent meter reading have been widely used in the field of electric power. But at the same time, there are still many deficiencies in China's power grid. Therefore, this paper puts forward the research of ubiquitous power Internet of things and IPv6 Technology in wireless access terminal and intelligent meter reading application. In this paper, the current types of distribution network are investigated, and the shortcomings of the current power grid are analyzed. In view of the existing power grid operation in China, this paper deeply studies the prospect of ubiquitous power Internet of things and IPv6 Technology in wireless access terminal and intelligent meter reading application, as well as the unique advantages of ubiquitous power Internet of things and IPv6 Technology in power grid. Through the relevant investigation, it can be seen that the service level, operation level, ecological environment construction and data sharing of the enterprise have been greatly improved after using ubiquitous power Internet of things and IPv6 technology. In addition, the power network structure has the advantages of simplifying network, reducing parameter setting, reducing communication flow and enhancing real-time data transmission. At the end of the study, this paper analyzes the key technology of ubiquitous power Internet of things in wireless access terminal and intelligent meter reading application, and puts forward a new research direction for the full application of the technology.